Nociception-induced spatial and temporal plasticity of synaptic connection and function in the hippocampal formation of rats: a multi-electrode array recording - Zhang Fu-Kang; Li Hua; Chen Xue-Feng; He Ying; Wang Dan-Dan; Wang Yan; Yuan Dong-Liang; Liu Ming-Gang; Zhao Xiao-Yan; He Xiao-Sheng; Chen Jun (SAGE Publishing, 2009)
Abstract Background Pain is known to be processed by a complex neural network (neuromatrix) in the brain. It is hypothesized that under pathological state, persistent or chronic pain can affect various higher brain functions through ascending pathways, leading to co-morbidities or mental disability of pain. However, so far the influences of pathological pain on the higher brain functions are less clear and this may hinder the advances in pain therapy. In the current study, we studied spatiotemporal plasticity of synaptic connection and function in the hippocampal formation (HF) in response to persistent nociception. Results On the hippocampal slices of rats which had suffered from persistent nociception for 2 h by receiving subcutaneous bee venom (BV) or formalin injection into one hand paw, multisite recordings were performed by an 8 × 8 multi-electrode array probe. The waveform of the field excitatory postsynaptic potential (fEPSP), induced by perforant path electrical stimulation and pharmacologically identified as being activity-dependent and mediated by ionotropic glutamate receptors, was consistently positive-going in the dentate gyrus (DG), while that in the CA1 was negative-going in shape in naïve and saline control groups. For the spatial characteristics of synaptic plasticity, BV- or formalin-induced persistent pain significantly increased the number of detectable fEPSP in both DG and CA1 area, implicating enlargement of the synaptic connection size by the injury or acute inflammation. Moreover, the input-output function of synaptic efficacy was shown to be distinctly enhanced by the injury with the stimulus-response curve being moved leftward compared to the control. For the temporal plasticity, long-term potentiation produced by theta burst stimulation (TBS) conditioning was also remarkably enhanced by pain. Moreover, it is strikingly noted that the shape of fEPSP waveform was drastically deformed or split by a TBS conditioning under the condition of persistent nociception, while that in naïve or saline control state was not affected. All these changes in synaptic connection and function, confirmed by the 2-dimentional current source density imaging, were found to be highly correlated with peripheral persistent nociception since pre-blockade of nociceptive impulses could eliminate all of them. Finally, the initial pharmacological investigation showed that AMPA/KA glutamate receptors might play more important roles in mediation of pain-associated spatiotemporal plasticity than NMDA receptors. Conclusion Peripheral persistent nociception produces great impact upon the higher brain structures that lead to not only temporal plasticity, but also spatial plasticity of synaptic connection and function in the HF. The spatial plasticity of synaptic activities is more complex than the temporal plasticity, comprising of enlargement of synaptic connection size at network level, deformed fEPSP at local circuit level and, increased synaptic efficacy at cellular level. In addition, the multi-synaptic model established in the present investigation may open a new avenue for future studies of pain-related brain dysfunctions at the higher level of the neuromatrix.